Analisis Sistem Informasi Akuntansi dalam Pembayaran Klaim Kecelakaan Lalu Lintas Jalan pada PT. Jasa Raharja (Persero) Kantor Cabang Sulawesi Selatan - Resky AN, Kiki Ananda; Idris, Hariany; Idrus, Mukhammad (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study aims to analyze the accounting information system for traffic accident insurance claim payments at PT Jasa Raharja. The research method in this thesis uses a qualitative approach. Data in this study were collected using observation, interview, and documentation methods. The data analysis method uses descriptive analysis methods. The results of this study indicate that the accounting information system for claim payments at PT JASA RAHARJA can be said to be quite good, this is indicated by the organizational structure and related sections that have clear functions and sections, the documents used, and the procedures applied are in accordance with the SOP applicable to Jasa Raharja.